Diffusion-weighted-preparation (D-prep) MRI as a future extension of SPECT/CT based surgical planning for sentinel node procedures in the head and neck area?. (September 2016) - Buckle, Tessa; KleinJan, Gijs H.; Engelen, Thijs; van den Berg, Nynke S.; DeRuiter, Marco C.; van der Heide, Uulke; Valdes Olmos, Renato A.; Webb, Andrew; van Buchem, Mark A.; Balm, Alfons J.; van Leeuwen, Fijs W.B.
Highlights: D-prep MRN enabled improved delineation of LNs. D-prep MRN enabled visualization of nerves in the areas that most often harbor SNs. A SPECT/MRI approach is envisioned for future surgical planning of complex SN resections. Abstract: Purpose: Even when guided by SPECT/CT planning of nodal resection in the head-and-neck area is challenging due to the many critical anatomical structures present within the surgical field. In this study the potential of a (SPECT/)MRI-based surgical planning method was explored. Hereby MRI increases the identification of SNs within clustered lymph nodes (LNs) and vital structures located adjacent to the SN (such as cranial nerve branches). Method and patients: SPECT/CT and pathology reports from 100 head-and-neck melanoma and 40 oral cavity cancer patients were retrospectively assessed for SN locations in levels I–V and degree of nodal clustering. A diffusion-weighted-preparation magnetic resonance neurography (MRN) sequence was used in eight healthy volunteers to detect LNs and peripheral nerves. Results: In 15% of patients clustered nodes were retrospectively shown to be present at the location where the SN was identified on SPECT/CT (level IIA: 37.2%, level IIB: 21.6% and level III: 15.5%). With MRN, improved LN delineation enabled discrimination of individual LNs within a cluster. Uniquely, this MRI technology also provided insight in LN distribution (23.2 ± 4 LNs per subject) and size (range 21–372 mm 3 ), and enabled non-invasive assessment of anatomical variances in the location of the LNs and facial nerves. Conclusion: Diffusion-weighted-preparation MRN enabled improved delineation of LNs and their surrounding delicate anatomical structures in the areas that most often harbor SNs in the head-and-neck. Based on our findings a combined SPECT/MRI approach is envisioned for future surgical planning of complex SN resections in this region.